Cultural aspects of proper names - Szulowska, Wanda (Papers in Linguistics, 2021)
The article discusses some cultural aspects and political developments that doubtlessly influence forms of proper names belonging to various name categories. In the case of first names the focus is put on various motivations for name choices made in the periods before and after Christianization. As far as the category of surnames is concerned, it is emphasized that surnames ending with the suffix -ski enjoy a dominant position in Poland, which was certainly caused by the nobility culture perceived as superior. On the other hand, the status of feminine personal names is discussed in connection with women’s legal situation in those times. The influence of later political developments on all categories of proper names is addressed as well. The article aims to draw readers’ attention to how political and social changes, as well as tradition impact the structure of the onymic system in the Polish language.